Relationship of oxidative stress to visceral adiposity in youth and role played by vitamin D. Issue 5 (8th June 2020) - Samouda, Hanen; De Beaufort, Carine; Gilson, Georges; Schritz, Anna; Vaillant, Michel; Ghaddhab, Chiraz; Ruiz‐Castell, Maria; Huiart, Laetitia; Dohet, François; Weber, Bernard; Bohn, Torsten
Abstract: Background: Visceral adipose tissue (VAT) accumulation is a major cardiometabolic risk factor, associated with increased inflammation. Oxidative stress (OS) is also associated with inflammation and cardiometabolic issues, yet mainly through general obesity. Both OS and obesity were linked to vitamin D deficiency. Objectives: To investigate whether OS increase is associated with VAT accumulation in youth, and whether in the presence of VAT accumulation, a higher vitamin D status is associated with lower OS. Methods: One hundred and fifty‐eight youth with overweight/obesity, 7 to 17 years old, were recruited (Pediatric Clinic, Luxembourg). We assessed visceral and subcutaneous abdominal adipose tissues by magnetic resonance imaging, OS by DNA/RNA oxidative damage with ELISA and vitamin D by high‐performance liquid chromatography. Results: VAT was the body fat compartment the most strongly associated with OS ( R Pearson : 0.298; P < 10 −4 ). The general linear (GLM) models assessing the relationship between OS, VAT and vitamin D concentrations showed that "Log10 OS = (0.003 × VAT) + 3.911 ( R 2 adjusted : 0.083; P ‐value < 10 −4 )"; "Log10 OS = (0.003 × VAT) – (0.156 × log10 vitamin D) + 4.110 ( R 2 adjusted : 0.101; P ‐value < 10 −4 )". After back‐transformation of the log‐values into normal values, the GLM showed that, for a person with an average value of VAT (40.7 cm 2 ), a 10 cm 2 increase in VAT would increase OS by approx. 771.833 pg/mL, after age, gender, Tanner stage and physical activity adjustment. An approximate increase of 9 ng/mL of vitamin D would counterbalance this negative effect of increased VAT. Conclusion: Dietary strategies improving vitamin D status should be investigated to tackle VAT and OS increase.